Objective assessment of skin rejuvenation using near-infrared 1064-nm neodymium: YAG laser in Asians - Tanaka Y; Matsuo K; Yuzuriha S (Dove Medical Press, 2011)
Yohei Tanaka1,2, Kiyoshi Matsuo1, Shunsuke Yuzuriha11Department of Plastic and Reconstructive Surgery, Shinshu University School of Medicine, Matsumoto, Japan; 2Clinica Tanaka Plastic and Reconstructive Surgery and Anti-aging Center, Matsumoto, JapanBackground: We reported previously that near-infrared (NIR) irradiation provides long-lasting stimulation of elastin, and is efficient for skin rejuvenation. Many studies have indicated the efficacy of various types of laser, but did not include sufficiently objective evaluation. Therefore, we evaluated the efficacy of NIR laser treatment not only subjectively but also objectively.Methods: Fifty Japanese patients were treated with a NIR 1064-nm neodymium: YAG laser. Objective computer assessments were performed by Canfield VISIA Complexion Analysis for improvement of dilated pores, skin texture, and wrinkles. The volunteers then provided subjective assessments. Histological evaluations of elastin were performed by Victoria blue staining up to 90 days post-treatment in four Japanese volunteers.Results: Mean pretreatment percentiles of dilated pores, skin texture, and wrinkles were 51.08 ± 24.82, 54.7 ± 26.33, and 58.02 ± 28.61, respectively. Mean post-treatment percentiles of dilated pores, skin texture, and wrinkles were 53.58 ± 23.89, 58.58 ± 24.44, and 62.2 ± 25.39, respectively. All objective computer assessments evaluated by percentiles in dilated pores, skin texture, and wrinkles showed significant improvement after NIR laser treatment. Ninety-six percent, 100%, and 98% of volunteers reported satisfaction with the improvement of dilated pores, skin texture, and wrinkles, respectively. NIR laser treatment appeared to increase the amount of elastin at day 30, which then decreased slightly but was still elevated at day 90 compared with nonirradiated controls on day 0. Thickening of the epidermis was detected on day 30, and epidermal smoothness persisted for up to 90 days. No treatment-related adverse events were observed.Conclusions: NIR irradiation increased elastin in the dermis, and achieved skin rejuvenation. The results indicated that NIR irradiation provides safe and effective long-term stimulation of elastin, which is beneficial for improving dilated pores, skin texture, and wrinkles.Keywords: near-infrared laser, elastin, skin rejuvenation, objective assessment